Confocal microscopy study of donor–recipient interface after Descemet's stripping with endothelial keratoplasty. Issue 7 (12th October 2009) - Espana, E M; Huang, B
Abstract : Aim: To evaluate the in vivo confocal microscopic corneal features seen in patients who underwent Descemet's stripping with endothelial keratoplasty (DSEK) and to correlate these findings with the postoperative best spectacle-corrected visual acuity (BSCVA) obtained at the time of confocal microscopy. Methods: Observational case series. A review of charts and confocal microscopy images and videos (Confoscan 4; Nidek Technologies America, Greensboro, North Carolina, USA) of 25 consecutive eyes from 21 patients who underwent DSEK for Fuchs' dystrophy or pseudophakic bullous keratopathy and had a follow-up of at least 6 months post-DSEK. Time from DSEK to confocal microscopy ranged from 6 to 22 months. Subepithelial haze, donor–recipient interface haze, interface birefringent particles and presence of stromal folds were evaluated by a blinded observer and correlated to the postoperative BSCVA. Results: 25 eyes (21 patients) with a mean age of 71.3 (11.8) years were included. A significant negative correlation was found between postoperative BSCVA and subepithelial corneal haze (Spearman correlation coefficient) (rs =−0.651; p=0.0004). Donor–recipient interface haze (rs =−0.0908; p=0.6658), interface particles (rs =−0.2403; p=0.2472) or the presence of stromal folds (rs =0.111; p=0.6055) did not correlate with BSCVA. Conclusion: Subepithelial haze, donor–recipient stromal interface haze, birefringent particles and stromal folds were present at different degrees in all patients who underwent DSEK. However, subepithelial haze was the only factor that correlated to postoperative BSCVA.